(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The problem with religion is its subjectivity it is a matter of faith. Hence, one finds it easier to oppose a creed to which one does not ascribe any significance. Nevertheless, political positions are also, in the end, “creeds” that one chooses to embrace. Literary works, as manifestations of a society, portray the political and religious aspects of the social realm in which they were produced. Our perception of an independent material world of objects, persons, and processes is grounded in a pervasive error. We take the unreal for the real and the real for unreal. This is borne out by the famous analogy of the snake and the rope. We often mistake a coil of rope for a snake in the dark but, on closer examination, we discover it to be only a coil of rope. Our everyday world of appearances may be likened to a snake, and it seems very real to us we are in the darkness of ignorance caught in the web of illusion. When we are illumined, According to Hinduism, the root of the never-ending suffering that human beings experience in the world of constant flux is craving. In Hinduism, the words of Krishna reveal the same idea “All is clouded by desire as the fire by smoke, as a mirror by dust, as an unborn baby by its covering. Wisdom is clouded by desire, the ever-present enemy of the wise, desire in its innumerable forms, which like a fire cannot find satisfaction”. T. S. Eliot, the prolific poet and literary critic, penned a work that created a great controversy among literary critics, the Four Quartets. For some, it is Eliot’s masterpiece for others, the work serves as proof that religious influence becomes counterproductive when explicitly manifested in a work of art. Despite the undercurrent against religion in the last century, religion is, and has always been, a manifestation of the highest ideals of the human beings and, therefore, to ignore its influence is futile. Even though there are people for whom religion ruins a work of art, one has to remember that religion, as a social manifestation, is as impossible to overlook as political concepts. Interestingly, while some critics eagerly banish works that include religious concepts, few people object to the genre known as political literature.